Study on Three Sarcocapnos Species as Potential Sources of Bioactive Compounds: Relation between Phenolic Content and Bioactivity by Multivariate Analysis - María del Pilar Fernández-Poyatos; Gökhan Zengin; Carlos Salazar-Mendías; Antonio Ruiz-Medina; Kouadio Ibrahime Sinan; Eulogio J. Llorent-Martínez (Journal of Analytical Methods in Chemistry)
In this work, we report the phenolic composition and bioactivity of the aerial parts of three species of Sarcocapnos (S. enneaphylla, S. pulcherrima, and S. saetabensis) to study their potential as sources of bioactive compounds to revalorize them and contribute to the conservation of these plant species. Samples were collected in different locations in the province of Jaén (southeast of Spain), and qualitative and quantitative analyses of phenolic compounds were performed by high-performance liquid chromatography with diode array and mass spectrometry detection. S. enneaphylla presented the highest concentration of phenolic compounds (58 mg/g DE). The most abundant compound in S. enneaphylla and S. saetabensis was rutin (35 mg/g DE and 11.7 mg/g DE, respectively), whereas isorhamnetin-O-rutinoside was dominant in S. pulcherrima (11.5 mg/g DE). Several assays were performed to evaluate the potential bioactivity of the three species of Sarcocapnos. These assays included antioxidant and radical scavenging (ABTS and DPPH), reducing power (CUPRAC and FRAP), phosphomolybdenum and metal chelating, and enzyme inhibitory activity (acetylcholinesterase, amylase, butyrylcholinesterase, glucosidase, and tyrosinase). In general, all methanolic extracts presented the highest phenolic and flavonoid contents, as well as the highest radical scavenging, antioxidant, and enzyme inhibitory properties. This relationship between phenolics and bioactivity was confirmed by multivariate analysis.